Model transformation as a mechanism for the implementation of domain specific transformation languages - Irazábal, Jerónimo (2010)
Model Driven Engineering proposes a software development process in which the key notions are models and model transformations. There are already several proposals for model transformation specification, implementation, and execution. In this paper we introduce the notion of domain specific transformation language (DSTL). A DSTL is a transformation language tailored for a specific domain; in contrast to well known transformation languages, such as QVT or ATL, the DSTL's syntax and semantics are directly related to a specific domain and/or kind of transformation. A DSTL makes transformations easer to write and understand, the code is intuitive and the users do not need to know a generic transformation language. Also we analyze a novel way to define its semantics. Our proposal consists in using transformation languages themselves to the implementation of such domain specific languages. We illustrate the proposal through an example in the database domain.